22 The influence of body mass index, glycemic control and vitamin D status on outcomes in patients admitted to intensive care with COVID-19: a single centre retrospective study. (12th April 2022) - Eden, Timothy; Neville, Jonathan; McAuliffe, Shane; Crocombe, Dominic; Ray, Sumantra
Abstract : Background: Coronavirus disease 2019 (COVID-19) is an inflammatory syndrome caused by a novel coronavirus (SARS-CoV-2). Symptoms range from mild infection to severe acute respiratory distress syndrome (ARDS) requiring ventilation and intensive care (ICU). 1 UK cases have exceeded 300, 000 with a fatality rate of 13% necessitating >10, 000 critical care admissions. 2 Nutrition is important to immune function and influences metabolic risk factors such as obesity and glycaemic control. Poor nutritional status is associated with worse outcomes in ARDS and viral infections yet limited research has assessed pre-morbid nutritional status and outcomes in patients critically unwell with COVID-19. 3 Objectives: Investigate the effect of body mass index, glycemic control and vitamin D status on outcomes in adult patients admitted to a ICU with COVID-19. Methods: Retrospective review of all patients admitted to a central London ICU between March-May 2020 with confirmed COVID-19. Electronic patient records data was analysed for patient demographics; co-morbidities; admission BMI; serum vitamin D concentration and plasma HbA1c. Serum vitamin D and HbA1c were measured on admission, or within one month of admission to ICU. Primary outcome was mortality. Secondary outcomes included time intubated, ICU stay duration, and ICU-related morbidity. Results: N = 72 patients; 54 (75%) male, mean age 57.1 (± 9.8) years. Overall mortality was 24 (33%). The highest rate was observed in the overweight BMI range (25-29.9kg/m2) p-value <0.001. In the survival arm admission HbA1c (mmol/mol) was lower 50.2 vs 60.8 but was not statistically significant. Vitamin D measures (n=51) correlated significantly higher mortality for individuals with vitamin D deficiency (<25 IU/L) 16%, p-value 0.013, versus no deaths in those with levels >50 IU/L (n=8). Discussion/Conclusion: There was a correlation between overweight and mortality, and possible (nonsignificant) association between glycaemic control and poor prognosis, as seen in larger observational studies. 4 5 Increased adiposity and deranged glucose homeostasis may potentially increase risk of COVID-19 infection and severity, possibly relating to impaired lung and metabolic function, increased proinflammatory and thrombotic mechanisms. Vitamin D deficiency associated with poorer outcomes and mortality, supporting a possible role of vitamin D in immune function specific to pulmonary inflammation and COVID-19 pathophysiology. 6 Further research is needed into specific nutritional markers influencing critical care admissions with COVD-19. References: Wang D, Hu B, Hu C, Zhu F, Liu X, Zhang J, et al . Clinical characteristics of 138 hospitalized patients with 2019 novel coronavirus–infected pneumonia in Wuhan, China. JAMA [Internet] 2020 Mar 17;323 (11):1061–9. Available from: https://doi.org/10.1001/jama.2020.1585 Intensive Care National Audit and Research Centre (ICNARC). ICNARC report on COVID-19 in critical care 31 July 2020. 2020. Loi M, Wang J, Ong C, Lee JH. Nutritional support of critically ill adults and children with acute respiratory distress syndrome: a clinical review. Clin Nutr ESPEN [Internet] 2017;19 :1–8. Available from: http://www.sciencedirect.com/science/article/pii/S2405457716303667 Apicella M, Campopiano MC, Mantuano M, Mazoni L, Coppelli A, Del Prato S. COVID-19 in people with diabetes: understanding the reasons for worse outcomes. Lancet Diabetes Endocrinol [Internet] 2020 Sep 1;8 (9):782–92. Available from: https://doi.org/10.1016/S2213-8587(20)30238-2 Sattar N, Ho FK, Gill JM, Ghouri N, Gray SR, Celis-Morales CA, et al . BMI and future risk for COVID-19 infection and death across sex, age and ethnicity: preliminary findings from UK biobank. Diabetes Metab Syndr [Internet] 2020 Jun 30;14 (5):1149–51. Available from: https://pubmed.ncbi.nlm.nih.gov/32668401 Lanham-New SA, Webb AR, Cashman KD, Buttriss JL, Fallowfield JL, Masud T, et al . Vitamin D and SARS-CoV-2 virus/COVID-19 disease. BMJ Nutr Prev Heal 2020;bmjnph-2020-000089.